Expiration-Triggered Sinus Arrhythmia Predicts Outcome in Survivors of Acute Myocardial Infarction - Sinnecker, Daniel; Dommasch, Michael; Steger, Alexander; Berkefeld, Anna; Hoppmann, Petra; Mueller, Alexander; Gebhardt, Josef; Barthel, Petra; Hnatkova, Katerina; Huster, Katharina M.; Laugwitz, Karl-Ludwig; Malik, Marek; et al. (Journal of the American College of Cardiology, 2016)
Background Respiratory sinus arrhythmia (RSA), a measure of cardiac vagal modulation, provides cardiac risk stratification information. RSA can be quantified from Holter recordings as the high-frequency component of heart rate variability or as the variability of RR intervals in individual respiratory cycles. However, as a risk predictor, RSA is neither exceptionally sensitive nor specific. Objectives This study aimed to improve RSA determination by quantifying the amount of sinus arrhythmia related to expiration (expiration-triggered sinus arrhythmia [ETA]) from short-term recordings of electrocardiogram and respiratory chest excursions, and investigated the predictive power of ETA in survivors of acute myocardial infarction. Methods Survivors of acute myocardial infarction (N = 941) underwent 30-min recordings of electrocardiogram and respiratory chest excursions. ETA was quantified as the RR interval change associated with expiration by phase-rectified signal averaging. Primary outcome was 5-year all-cause mortality. Univariable and multivariable Cox regression was used to investigate the association of ETA with mortality. Results ETA was a strong predictor of mortality, both in univariable and multivariable analysis. In a multivariable model including respiratory rate, left ventricular ejection fraction, diabetes mellitus, and GRACE score, ETA ≤0.19 ms was associated with a hazard ratio of 3.41 (95% confidence interval: 1.10 to 5.89, p < 0.0001). In patient subgroups defined by abnormal left ventricular ejection fraction, increased respiratory rate, high GRACE score, or presence of diabetes mellitus, patients were classified as high or low risk on the basis of ETA. Conclusions Expiration-triggered sinus arrhythmia (ETA) is a potent and independent post-infarction risk marker.
CRIS-Team Scopus Importer:2023-03-08
Keywords: heart rate variability; phase-rectified signal averaging; respiratory sinus arrhythmia; risk stratification